Analysis of factors that drives arthrocentesis for suspected septic joint. (April 2021) - Roth, Cameron A.; Da Lomba, Tony; Dadwani, Rahul; Dahm, James; Strelzow, Jason
Introduction: This study aims to develop a simple diagnostic criterion that could be used to justify arthrocentesis in adults with suspected septic arthritis. Our hypothesis is that no single factor will be predictive for a decision to aspirate a questionable septic joint. Methods: A prospective observational cohort study was performed at a Level 1 Trauma institution including all patients over the age of 18 years referred to Orthopaedics through the Emergency Department or inpatient orthopaedic consultations for a suspected septic joint. Patient information recorded was age, laboratory markers (white blood cell count, erythrocyte sedimentation rate, C-reactive protein, physical exam findings (fever, pain with range-of-motion), and presence of smoking, diabetes, end-stage renal disease (ESRD) on dialysis, and body mass index > 30. Continuous data was analyzed using logistic regression, and nominal data was analyzed using a two-tailed Fisher's exact test. Results: A total of 128 patients met inclusion criteria for this study; 71 patients underwent arthrocentesis for suspected septic joint. On analysis of risk factors, the demographics, laboratory markers, physical exam and comorbidities were not significant between the two groups. On subset analysis of the septic joints, we found the only risk factor to be significantly predictive of whether a joint was septic was the presence of ESRD on dialysis ( p  = 0.042). Conclusion: Past data have looked solely at predictive risk factors for septic arthritis; however, this study aims to predict what drives physicians towards aspirating a joint even before it is determined to be septic. We found no single factor was predictive of joint aspiration. Only ESRD on dialysis is predictive of whether a joint with concern for septic arthritis would ultimately be septic in our institution. The decision to aspirate continues to be best determined by clinician judgment in light of experience and available clinical information.